The impact of ondansetron on clinical outcomes in cranial surgery patients: a propensity-matched analysis of retrospective data - Yun, Debo; Luo, Yongzhen; Li, Rui; Li, Wenyong; Wan, Chunyou; Huang, Qinjiang; Du, Jiang; Zeng, Shiyi; Wang, Guangdong (Frontiers in Aging Neuroscience, 2025)
IntroductionCranial surgery represents a substantial public health challenge, characterized by intricate postoperative management that can complicate patient recovery. This study investigates the effect of ondansetron, a serotonin receptor antagonist, on clinical outcomes in adult patients undergoing cranial surgery, addressing the uncertainty surrounding its impact on postoperative complications.MethodsUtilizing a retrospective cohort design, we analyzed data from 2,297 eligible patients, segregating them into ondansetron-treated and control groups, while applying propensity score matching to harmonize baseline characteristics. The primary outcomes assessed were 28-day and 90-day mortality, evaluated using multivariable Cox regression and Kaplan-Meier analysis.ResultsAfter matching, 905 well-balanced pairs were included. Ondansetron administration was associated with significantly lower 28-day mortality (hazard ratio [HR] = 0.69, 95% confidence interval [CI]: 0.52–0.92; P = 0.012) and 90-day mortality (HR = 0.74, 95% CI: 0.58–0.94; P = 0.014) after adjusting for potential confounders. Kaplan-Meier survival analysis further corroborated these findings, showing a consistent protective effect of ondansetron with significant mortality reduction at both 28 days (HR = 0.68, 95% CI: 0.51–0.91; P = 0.009) and 90 days (HR = 0.75, 95% CI: 0.59–0.95; P = 0.015), with subgroup analyses confirming result stability across demographic factors.ConclusionThe administration of ondansetron in cranial surgery patients with a Glasgow Coma Scale score exceeding eight is associated with a significant reduction in short-term mortality, suggesting that ondansetron could be a viable therapeutic strategy to enhance postoperative recovery outcomes.